An annotated catalogue of the spider wasps (Hymenoptera: Pompilidae) of Russia - Loktionov, Valery M.; Lelej, Arkady S. (Zootaxa, 2017)
Two hundred and forty-four valid species in 36 genera are listed. The genus Telostegus Costa, 1887 with the species T. inermis (Brullé, 1833) are newly recorded from Russia. Lectotypes are designated for Salius desertorum F. Morawitz, 1891, Psammochares amurensis Gussakovskij, 1932, and Pompilus cardinalis F. Morawitz, 1891. The generic status of Batozonellus Arnold, 1937, stat. resurr. is reinstated. Five taxa: Ceropales pygmaea pygmaea Kohl, 1880, C. ruficornis Gussakovskij, 1931, Eoferreola anatolica Priesner, 1973, Hemipepsis sinensis (Smith, 1855), and Telostegus nigritulus (Klug, 1834) are excluded from the list of the Russian fauna. The world number of genus-group names of Pompilidae is clarified: 451 nominal names, including 42 unavailable names, were proposed. Of the 409 available names, 254 are currently considered valid.